Archaeology : The Discipline of Things - Olsen, Bjornar (Book collections on Project MUSE., 2012)
Archaeology has always been marked by its particular care, obligation, and loyalty to things. While archaeologists may not share similar perspectives or practices, they find common ground in their concern for objects monumental and mundane. This book considers the myriad ways that archaeologists engage with things in order to craft stories, both big and small, concerning our relations with materials and the nature of the past. Literally the "science of old things," archaeology does not discover the past as it was but must work with what remains. Such work involves the tangible mediation of pa.